Coaching Without Going Through the Court Against Suspected Jarimah Violators By Satpol PP and Wh Lhokseumawe - Dirmawan Suryadi; Mohd. Din; Ali Abubakar (International Journal of Law and Society, 2025)
In Aceh, the provision of guidance is regulated in Articles 5 and 6 of Gubenur Regulation Number 139 of 2016, which states that the main task and function of the Civil Service Police Unit and Wilayatul Hisbah Aceh is the guidance function. Article 1 point 14 of Qanun Number 7 Year 2013 on Jinayat Procedure Law states that the function of Wilayatul Hisbah (WH) is to socialise, supervise, enforce, and foster the implementation of Islamic Sharia. Therefore, there is a problem of interpreting the authority of coaching carried out by Satpol PP and WH of Lhokseumawe City. This study aims to determine the legal basis for the coaching of suspected jarimah violators by Satpol PP and WH of Lhokseumawe City and the legal consequences of coaching suspected jarimah violators without going through the judicial process carried out by Satpol PP and WH of Lhokseumawe City. The research method used is empirical juridical. Data sources are obtained through interviews with respondents and informants. The results of this study indicate that the coaching carried out by Satpol PP and WH of Lhokseumawe city against suspected jarimah violators does not have a clear legal basis. The coaching carried out is only based on a statement signed by the alleged jarimah violator during the investigation and the legal consequences of coaching against jarimah offenders by Satpol PP and WH of Lhoseumawe City without going through the judicial process is carried out without a legal basis which results in serious legal consequences such as the coaching is not legally valid (can be cancelled), violates human rights, and can be sued civilly or criminally prosecuted and reduces public confidence in Sharia law.